Application of Beauveria bassiana (Bals.) Vuil. (Hypocreales: Cordycipitaceae) in rice seed and its effect on mortality of green leaf hopper, Nephotettix virescens (Distant) (Homoptera: Cicadellidae). Issue 1 (April 2020) - Abdullah, T; Kuswinanti, T; Nurariaty, A; Daud, I D; Nasruddin, A; Risal, R; Utami, S; Tuwo, M
Abstract: The use of synthetic chemical insecticides in controlling rice pest insects has various negative impacts. Chemical insecticides can stimulate pest resistance, the emergence of secondary pests, killing of useful organisms and natural enemies, and contamination of residues in food, soil and water. Another potential effective control alternative is the use of entomopathogenic fungus Beauveria bassiana (Bals.) Vuil. (Hypocreales: Cordycipitaceae). The effectiveness of B. bassiana application by spraying on plants or pests directly, can decrease due to the influence of high temperatures, low humidity, and exposure to ultra violet light. The study of the application of B. bassiana by treatment of rice seeds was carried out to determine the cumulative mortality of green leaf hopper, which was carried out in two-time periods at the Bioecology Laboratory for Natural Pests and Enemies, Department of Plant Pests and Diseases, Faculty of Agriculture, Hasanuddin University. The first series of studies used B. bassiana collection culture of Bioecology Laboratory, and the second series used the commercially available B. bassiana formulation. Completely Randomized Design (CRD), with each of the 4 treatments and 5 replications was used in this study. The results showed that, coating or soaking rice seeds with entomopathogenic fungi B. bassiana was able to cause mortality to green leafhoppers. Although the mortality is lower than spraying on rice plants or penetrating the body of green leafhoppers, however, with the covering or soaking rice seeds, the mortality of green leafhoppers is significantly higher than control without the application of B. bassiana . This indicates basic potential that requires a study for development of rice seed coating and immersion techniques to increase its effectiveness in controlling green leafhoppers.